Book one : shipwreck : island - Korman, Gordon (Scholastic Inc., 2001)
Book one: shipwreck Island Luke, J. J., Will, Lyssa, Charla, and Ian. They didn't want to be on boat in the first place. they didn't want to bo stuck at sea with a bunch of strangers. But when you're in the middle of the Pacific Ocean, there's no easy way ait. And when a terrifying storm hits, there's no way to fully prepare. It's all about survival.